1995
DOI: 10.1037/0278-7393.21.6.1395
|View full text |Cite
|
Sign up to set email alerts
|

Automaticity and word perception: Evidence from Stroop and Stroop dilution effects.

Abstract: The Stroop effect is cut in half by adding a neutral word to the display. D. Kahneman and D. Chajczyk's (1983) "attention capture" account of "Stroop dilution" holds word recognition to be involuntary but strictly serial. The authors compared attention capture to 3 alternatives involving parallel rather than serial processing: In the lexicon, activation is divided among multiple words; postlexically, multiple words race for access to response processes; or prelexically, feature processing is degraded by multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
4
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(168 citation statements)
references
References 57 publications
11
150
4
2
Order By: Relevance
“…The neutral word diluter eliminated the compatibility effect originating in the distractor words LEFT or RIGHT but had no effect on the influence of a left or right distractor arrow [F(1,94) 11.69, MS e 699, p .001]. Previous studies showed that some amount of dilution occurs regardless of the nature of the diluter (Brown et al, 1995;Kahneman & Chajczyk, 1983;Mitterer et al, 2003), but the present results indicate that the success of word diluters in reducing the compatibility effect is strongly dependent on the nature of the distractor that is the source of the compatibility effect. Alternatively, the symbol diluter produced only a small and nonsignificant reduction in the compatibility effect, regardless of whether this effect originated in a word or a symbol distractor was run for the factors of compatibility (compatible vs. incompatible) and diluter condition (no diluter vs. symbol diluter vs. word diluter).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The neutral word diluter eliminated the compatibility effect originating in the distractor words LEFT or RIGHT but had no effect on the influence of a left or right distractor arrow [F(1,94) 11.69, MS e 699, p .001]. Previous studies showed that some amount of dilution occurs regardless of the nature of the diluter (Brown et al, 1995;Kahneman & Chajczyk, 1983;Mitterer et al, 2003), but the present results indicate that the success of word diluters in reducing the compatibility effect is strongly dependent on the nature of the distractor that is the source of the compatibility effect. Alternatively, the symbol diluter produced only a small and nonsignificant reduction in the compatibility effect, regardless of whether this effect originated in a word or a symbol distractor was run for the factors of compatibility (compatible vs. incompatible) and diluter condition (no diluter vs. symbol diluter vs. word diluter).…”
Section: Discussionmentioning
confidence: 99%
“…As in Experiment 1, the symbolic diluter led to a small (5-msec) reduction in the compatibility effect that also did not reach significance [t (48) influence the effect of diluters in the Simon task. First, Brown et al (1995) concluded that the magnitude of the Stroop dilution effect is at least partially determined by the visual complexity of the diluters, as compared with the distractors, with relatively more complex diluters leading to greater visual interference. Applying this logic to the present case, the complexity of the diluters relative to the distractors would have been less in Experiment 1 than in Experiment 2, since the distractors were words versus a single repeating symbol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For that reason, despite a fair amount of research searching for an appropriate baseline, researchers have not settled on one. As a result, many researchers (e.g., Brown, Roos-Gilbert, & Carr, 1995;Kahneman & Chajczyk, 1983;Logan & Zbrodoff, 1979) have compared performance for congruent stimuli with performance for incongruent stimuli rather than comparing performance for both with performance for neutral stimuli, just as Lindsay and Jacoby did.…”
Section: Dissociation Of the Stroop Taskmentioning
confidence: 99%